CULTURE AND LANGUAGE TEACHING THROUGH MEDIA - Bekmirzayeva Dilorom; G’aniyeva Tohira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The topic of teaching and learning culture has been a matter of considerable interest to language educators and much has been written about the role of culture in foreign language instruction over the past two decades. ESL students whose success in a new environment is conditioned not only by their mastery of the new language, but also, and especially, by their ability to negotiate the new culture.